2014
DOI: 10.5812/aapm.12091
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine-Sufentanil Versus Bupivacaine-Fentanyl in Spinal Anesthesia of Patients Undergoing Lower Extremity Surgery

Abstract: Background:The addition of intrathecal opioids to local anesthetics seems to improve the quality of analgesia and prolong the duration of analgesia, when using a subarachnoid block in Iranian patients with their specific pain tolerance.Objectives:The aim of this study was to evaluate the effects of adding fentanyl or sufentanil, to intrathecal bupivacaine, in terms of the onset and duration of; sensory block, motor block, hemodynamic effects and postoperative pain relief.Patients and Methods:This randomized cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…30% of patients in sufentanil group reached this level while only 5% in fentanyl group reached this level. [ 7 ] It was comparable to our findings. In another study comparing intrathecal fentanyl and sufentanil for endoscopic urological procedures, it was found that the maximal block height achieved by sufentanil group was (T10-T11) while fentanyl group was (T8-T11), which was significantly lower level achieved than our findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…30% of patients in sufentanil group reached this level while only 5% in fentanyl group reached this level. [ 7 ] It was comparable to our findings. In another study comparing intrathecal fentanyl and sufentanil for endoscopic urological procedures, it was found that the maximal block height achieved by sufentanil group was (T10-T11) while fentanyl group was (T8-T11), which was significantly lower level achieved than our findings.…”
Section: Discussionsupporting
confidence: 92%
“…The pain scores were significantly lower with sufentanil group. [ 7 ] The onset of sensory block was delayed in fentanyl and sufentanil group as compared to control group in another study. The difference may be due to the lower dose of bupivacaine used in fentanyl, sufentanil group (5 mg) as against control group (7 mg).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In more recent studies, it was proposed that adding sufentanil to intrathecal bupivacaine may prolong the duration of analgesia and facilitate the spread of sensory block ( 13 ). Studying patients with a history of drug abuse has its own challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil intrathecal administration can significantly shorten the onset time of anesthesia, improve the analgesic property of intrathecal anesthesia, and prolong the duration of analgesia [ 9 13 ]. Hassani et al [ 14 ] found that the effect of the addition of sufentanil to maintain hemodynamic stability was similar to the effect of fentanyl. Intrathecal sufentanil added to bupivacaine, as compared with fentanyl, may prolong duration of analgesia, facilitate the spread of the sensory block, increase mean pulse oximetry levels, and reduce overall adverse effects.…”
Section: Introductionmentioning
confidence: 99%